Age based analysis of Challenges of Banking Industry in India on the account of digitalization of Banks - Mishra, Dr. K N (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The banking industry is currently facing a precedence changes as if moves towards digitization. Due to many technological revolution in the banking field there are still challenges that are to be overcome. There is a need of new ideas and methods for accomplishing tasks on a greater role with customer at the forefront of the future. E-banking in India is still in its early stage of growth and development. Changing technology and tought competition have change the face of banking. Basically electronic banking is the use of computer to retrieve and process banking data and to initiate into transactions directly with a bank via a tele communication network. In other words the banking is the wave of future. E-banking brings host opportunities as well as, poses new challenges for authorities in regulating and supervising the financial system and in designing and implementing the macro-economic policy. Keywords : Banking Industry, Revolution, Digitalization, Changing Technology.